Doing SLA research with implications for the classroom : reconciling methodological demands and pedagogical applicability - DeKeyser, Robert; Botana, Goretti Prieto (Amsterdam ; Philadelphia : John Benjamins Publishing Company, 2019)
'This book is unique in bringing together studies on instructed second language acquisition that focus on a common question:'What renders this research particularly relevant to classroom applications, and what are the advantages, challenges, and potential pitfalls of the methodology adopted?' The empirical studies feature experimental, quasi-experimental and observational research in settings ranging from the classroom to the laboratory and CALL contexts. All contributors were asked to discuss issues of cost, ethics, participant availability, experimental control, teacher collaboration, and student motivation, as well as the generalizability of findings to different kinds of educational contexts, languages, and structures. This volume should be of interest to graduate students in second language research, practicing teachers who want some guidance to navigate the sometimes overwhelming array of publications, and to researchers who are planning studies on instructed second language learning or teaching and are looking to make principled decisions on which of the existing methodologies to adopt'--
Current research on instructed second language learning : a bird's eye view / Robert DeKeyser and Goretti Prieto Botana -- Observing language-related episodes in intact classrooms : context matters! / Laura Collins and Joanna White -- Metacognitive instruction and corrective feedback : methodological strengths, challenges, and joys of classroom-based quasi-experimental research / Masatoshi Sato and Shawn Loewen -- Integrating instructed second language research, pragmatics, and corpus-based instruction / Kathleen Bardovi-Harlig, Sabrina Mossman and Yunwen Su -- The roles of explicit instruction and guided practice in the proceduralization of a complex grammatical structure / Natsuko Shintani -- The effects of recasts versus prompts on immediate uptake and learning of a complex target structure / Hossein Nassaji -- The effects of multiple exposures to explicit information : evidence from two types of learning problems and practice conditions / Goretti Prieto Botana and Robert DeKeyser -- CALL in ISLA : promoting depth of processing of complex L2 Spanish'para/por' prepositions / Ronald P. Leow, Luis Cerezo, Allison Caras and Gorky Cruz -- Lexical development in the writing of intensive English program students / Alan Juffs -- Discussion: Balancing methodological rigor and pedagogical relevance / Nina Spada.
Includes bibliographical references and index.
Keywords: Second language acquisition -- Research -- Methodology; Language and languages -- Study and teaching -- Research -- Methodology